Processing the Raw: the Negative Reception of a Late-Medieval Hell Painting in Nineteenth-Century Denmark - Sadan, Ronah (Periskop – Forum for kunsthistorisk debat, 2023)
In 1883, a late-medieval wall painting of the Last Judgment was discovered under white-wash in the vault of Sædinge Church in Lolland, Denmark, and then quickly covered up again. The painting depicted, in part, a hell scene deemed too offensive to display. A documentary drawing executed upon the painting’s uncovering contains within it the conflicted reception that this scandalous image received within the aesthetic and devotional context of the nineteenth century. Through this case of an image’s uncovering, documentation, and concealment, this article examines various understandings of negativity: as damnation, as aesthetic insufficiency, as devotional decadence, and finally, as absence.